Extensive influence of microsporidian infection on sucrose solution consumption, antioxidant enzyme activity, cell structure, and lifespan of Asian honeybees - Fan, Xiaoxue; Zhao, Haodong; Zang, He; Dong, Shunan; Qiu, Jianfeng; Song, Yuxuan; Li, Kunze; Jiang, Haibin; Wu, Ying; Lü, Yang; Zhou, Dingding; Fu, Zhongmin; et al. (Frontiers in Immunology, 2024)
Apis cerana is the original host of Vairimorpha (Nosema) ceranae, a widespread fungal parasite that causes bee nosemosis, which severely threatens the health of bee colonies and the sustainable development of the apiculture industry. To evaluate the impact of V. ceranae infection on A. c. cerana workers, V. ceranae spores were purified and used to inoculate newly emerged workers to evaluate the effects of V. ceranae infection. This was followed by an in-depth investigation of V. ceranae spore load and host sucrose solution consumption. Activities of four major antioxidant enzymes (SOD, PPO, CAT, and GST) were determined. Paraffin sections of the host midgut tissue were prepared and subjected to microscopic observation. The survival rates of V. ceranae-inoculated and uninoculated workers were analyzed. The results showed that spore load gradually increased and peaked at 12 dpi. The consumption of workers in the V. ceranae-inoculated group was extremely significant higher (P < 0.0001) than that of workers in the un-inoculated group. The results of antioxidant enzyme activity were suggestive of positive host defense via catalase (CAT) and glutathione-S-transferase (GST) in the middle stage of infection, as well as the negative fungal impact on superoxide dismutase (SOD) and polyphenol oxidase (PPO) at the whole stage of infection, reflecting the complex host-parasite interaction. Additionally, we observed a disruption in the structure of the host midgut epithelial cells. Moreover, the survival rate of workers in V. ceranae-inoculated groups was nearly always lower than that of workers in the uninoculated groups. These results demonstrate a consistent increase in spore load with the proliferation of V. ceranae, leading to persistent energetic stress and midgut epithelial cell structural damage to the host, ultimately resulting in a shortened lifespan for the host. Our findings enhance the current understanding of the interactions between A. cerana and V. ceranae as well as provide a solid basis for exploring the mechanisms underlying host response and V. ceranae infection.